Socialism in the Twenty-First Century and Neo-liberalism: Diverse Ideological Options Do Not Always Generate Different Effects - Fernando Eguren (Revue Internationale de Politique de Développement)
This chapter seeks to demonstrate that policies derived from different ideological options do not necessarily generate significantly different effects. In the Andean region, the governments of Rafael Correa, in Ecuador, and Evo Morales, in Bolivia, have been following a political line of ‘twenty-first century socialism’, while the governments of Colombia and Peru have directed their political orientations towards neo-liberalism and the ‘Washington Consensus’. Nevertheless, two issues of importance—namely, the handling of the processes involved in the concentration of property land rights and the treatment of indigenous populations—demonstrate that the actions of these two groups of countries have not led to very different results. The fact that these countries have become part of the globalisation process has permitted variations in the relative radicalism of the governments’ political discourses but has led to significantly less flexibility with regard to the degree of autonomy that these governments face for implementing policies. Additionally, domestic social conflicts have set limits on the states’ abilities to manoeuvre when implementing their policies.